2021
DOI: 10.5694/mja2.51043
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depression and anxiety symptoms during the COVID‐19 pandemic in a representative Australian adult cohort

Abstract: Objectives To estimate initial levels of symptoms of depression and anxiety, and their changes during the early months of the COVID‐19 pandemic in Australia; to identify trajectories of symptoms of depression and anxiety; to identify factors associated with these trajectories. Design, setting, participants Longitudinal cohort study; seven fortnightly online surveys of a representative sample of 1296 Australian adults from the beginning of COVID‐19‐related restrictions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
114
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 28 publications
12
114
2
Order By: Relevance
“…Despite this attenuated impact, various studies point to an immediate impact on outcomes of well-being and distress in Australia, particularly in at-risk population groups [ 45 - 48 ]. For instance, Batterham et al [ 49 ] found that participants in Australia who had financial distress, social impairment, and work impairment were most impacted. Similarly, Li et al [ 50 ] found that young people, who due to their age are already at higher risk of mental health problems, showed elevated mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this attenuated impact, various studies point to an immediate impact on outcomes of well-being and distress in Australia, particularly in at-risk population groups [ 45 - 48 ]. For instance, Batterham et al [ 49 ] found that participants in Australia who had financial distress, social impairment, and work impairment were most impacted. Similarly, Li et al [ 50 ] found that young people, who due to their age are already at higher risk of mental health problems, showed elevated mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results may only be generalized to this group. Since various studies suggest that women in particular suffered from mental health issues during the early lockdown restrictions (Batterham et al, 2021;Fancourt et al, 2021;Saunders et al, 2021), our results may be valid for the most relevant population.…”
Section: Discussionmentioning
confidence: 74%
“…The PSIW scores proved to be a promising measure for investigating lockdown-dependent effects. Our sample comprised almost exclusively adult women, who were the most negatively affected by lockdown measures in the early stage of the COVID-19 pandemic (Batterham et al, 2021;Fancourt et al, 2021;Saunders et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations